Now you see me [videorecording (DVD)] - Leterrier, Louis, 1973-; Eisenberg, Jesse, 1983-; Harrelson, Woody; Fisher, Isla, 1976-; Freeman, Morgan; Ruffalo, Mark; Laurent, Mélanie, 1983-; Franco, Dave, 1985- (Summit Entertainment, 2013)
An elite FBI squad in a game of cat and mouse against ₁The Four Horsemen₂, a super-team of the world's greatest illusionists. The Four Horsemen pull off a series of daring heists against corrupt business leaders during their performances, showering the stolen profits on their audiences while staying one step ahead of the law.